ANALISIS HUMAN ERROR DI DEPARTEMEN BUBUT DENGAN METODE SHERPA - Karim, Abdul Alimul; Parhaeni, Parhaeni; Leksono, Vridayani Anggi; Nur, Muhammad (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
Manual work activities are more dependent on the operator's ability which still makes frequent Errors. One of the mistakes that occurs is due to human negligence or human Error. Human Error in manual work can result in work accidents. Even if human Error occurs frequently, it can result in a decrease in the efficiency and effectiveness of the company. Lathe activities at PT. C still uses the machine manually. Lathe work activities include the process of installing the lathe tool, picking up the workpiece, setting up the workpiece and the turning process. However, in these activities, there are still many human Errors that occur so that they affect the production of lathes. So it is necessary to improve operator performance in order to reduce human Error. For this reason, it is necessary to identify activities that have the potential for human Error. Work activities are broken down into task levels. Task levels are used as inputs to identify and analyze human Error qualitatively. This method is known as the SHERPA method. This study aims to find out the type of Error in each sub-task of the lathe process and provide recommendations to reduce the human Error that occurs. This research involved all lathe operators at PT. C. and validity is carried out to practitioners to produce consensus. The results of human Error analysis using the SHERPA method found three types of human Errors in the lathe process, action Error, selection Error and information communication Error. So, to reduce the prediction of Errors, it is recommended to train operators, relayout the production floor, increase K3 awareness, increase accuracy and comprehensive communication.